2005
DOI: 10.1088/1009-0630/7/1/023
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Screening in Xylanase-Producing Strains by Ion Implantation

Abstract: With ion implantation (N+, energy 10 keV and dosage 1.56 x 1015 N+ cmP2), a high xylanase-producing strain Aspergillus niger N212 was selected. Based on an orthogonal experiment, an optimal fermentation condition was designed for this high-yield strain. The suitable medium was composed of 8% corncob; 1.0% wheat bran; 0.1% TWEEN20; 0.5% (NH4)2S04; 0,5%NaN03; 0.5%FeS04, 7.5 x MnS04.Hz0, 2.5 x ZnSO4, 2.0 x CoC12, 3.0 x At present, under our experiment condition, xylanase activity of Aspergillus niger N212 reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Because of the very low survival rate, namely below 4%, with the implantation at the energy of 15 keV, the implantation was then carried out with an energy of 10 keV. These results are identical with other study [20] in which E. coli was used as the implanted organism.…”
Section: Determination Of N + Implantation Parameterssupporting
confidence: 80%
“…Because of the very low survival rate, namely below 4%, with the implantation at the energy of 15 keV, the implantation was then carried out with an energy of 10 keV. These results are identical with other study [20] in which E. coli was used as the implanted organism.…”
Section: Determination Of N + Implantation Parameterssupporting
confidence: 80%
“…The results showed that the optimum implanting ion species is N + . It has been well proven that N + has a higher mutation rate and a wider mutation spectrum than other ion species [19] . By means of N + implantation the mutant strain AF-ANm16, that does not produce red pigment in the fermentation process, was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing sugars and xylanase activity were determined with 3,5 dinitrosalicylic acid [13] . The enzymatic activities of the samples were determined after centrifuging the cultures for 20 min at 1000 g at the room temperature.…”
Section: Assay Of Xylanase Activitymentioning
confidence: 99%
“…In order to obtain the highest positive mutation and survival rate, 10 keV was chosen as the optimum energy based on the theory in Ref. [13] The survival rate was also related to the dose of N + implantation. A characteristic curve is shown in Fig.…”
Section: Determination Of N + Implantation Parametermentioning
confidence: 99%